IMPROVING PRODUCTION EFFICIENCY AND MARKET COMPETITIVENESS OF TRADITIONAL FOOD PRODUCTS: THE CASE OF KUE BANGKIT AND DODOL IN BATUBARA, INDONESIA - Sirojuzilam; Suria Sulaiman; Inggrita Gusti Sari Nasution; Dewi Ratna Sari Simatupang; Beby Kendida Hasibuan (RADJA PUBLIKA, 2024)
This study examines the impact of interventions aimed at improving the production efficiency and market competitiveness of traditional food products, particularly Kue Bangkit and Dodol, produced by “UD. Risa” in Batubara, Indonesia. The interventions included providing modern production equipment such as a santan (coconut milk) extractor and a dough mixer. The study shows that these interventions significantly reduced production time, improved product appeal, and increased market competitiveness, potentially opening up opportunities for local and international expansion. This study contributes to the body of knowledge on rural SME development, specifically in food production, and supports sustainable economic growth in rural areas.